2018
DOI: 10.3390/jimaging4060076
|View full text |Cite
|
Sign up to set email alerts
|

Single-Shot X-ray Phase Retrieval through Hierarchical Data Analysis and a Multi-Aperture Analyser

Abstract: Abstract:A multi-aperture analyser set-up was recently developed for X-ray phase contrast imaging and tomography, simultaneously attaining a high sensitivity and wide dynamic range. We present a single-shot image retrieval algorithm in which differential phase and dark-field images are extracted from a single intensity projection. Scanning of the object is required to build a two-dimensional image, because only one pre-sample aperture is used in the experiment reported here. A pure-phase object approximation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Another nonconventional technique, namely Edge Illumination (EI), has evolved simultaneously to the Talbot-Lau interferometer, yielding images very similar to DIC and DPC. The report from Marco Endrizzi from Alessandro Olivio's group at University College London (UCL) is the latest hallmark in data analysis from EI imaging [11]. Endrizzi's method first reduces pixel sampling by binning to avoid artifacts which arise from high-frequency noise.…”
Section: Data Methods and Resultsmentioning
confidence: 99%
“…Another nonconventional technique, namely Edge Illumination (EI), has evolved simultaneously to the Talbot-Lau interferometer, yielding images very similar to DIC and DPC. The report from Marco Endrizzi from Alessandro Olivio's group at University College London (UCL) is the latest hallmark in data analysis from EI imaging [11]. Endrizzi's method first reduces pixel sampling by binning to avoid artifacts which arise from high-frequency noise.…”
Section: Data Methods and Resultsmentioning
confidence: 99%
“…A single frame collected with a system like the one depicted in Fig 1(a) will contain a mixture of attenuation, differential phase and dark field contributions. Although we have started to develop methods that, under special conditions, enable the retrieval of more than one contrast channel from a single input image [22], broadly speaking multiple input frames are required to separate phase, attenuation and dark field images. Still with reference to Fig.…”
Section: Built For Speed: Single-shot Phase Retrievalmentioning
confidence: 99%
“…We recently showed that "multi-aperture" EI setups allow combining high phase sensitivity with large dynamic range in USAXS measurements [38], while opening the way to single-shot retrieval of multiple contrast channels [22]. In parallel, we have started to experiment with lab-based focusing of low-energy x-rays to further increase the phase sensitivity in soft matter applications, an example of which is provided in figure 4.…”
Section: Recent Developments and Future Directionsmentioning
confidence: 99%